Stenotrophomonas maltophilia G17: Potential antifungal agent isolated from the gut of black soldier fly larvae against Ganoderma boninense (Kuwait Journal of Science)
Oil palm (Elaeis guineensis Jacq.) is the primary source of foreign exchange in Indonesia's plantation sector. However, these plants are very vulnerable to attack by Ganoderma spp., which causes basal stem rot (BSR) and upper stem rot (USR) disease, resulting in significant economic losses. In this study, antagonistic assays of the G17 isolate obtained from the gut of black soldier fly (BSF) larvae showed potential biocontrol against G. boninense. Furthermore, antibiosis assays showed that the Stenotrophomonas maltophilia G17 isolate inhibited the growth of G. boninense by up to 85.56%–91.98%. Molecular identification using 16S rRNA, reinforced by biochemical characterization tests, confirmed the G17 isolate as S. maltophilia. Growth test results showed that S. maltophilia G17 cannot grow at a temperature of 37 °C within 24 h. The isolate also exhibited negative hemolytic activity, indicating it is not a pathogenic bacterium. S. maltophilia G17 exhibited lytic enzymes such as proteolytic, lipolytic, and chitinolytic activity. Among them, chitinolytic enzymes might be involved in the biocontrol process. © 2024 The Authors